Spatial confinement effects employed by metallic blocker and Ar gas pressures on laser-induced breakdown spectroscopy and surface modifications of laser-irradiated Mg. (3rd April 2017) - Hayat, A.; Bashir, S.; Rafique, M. S.; Ahmed, R.; Akram, M.; Mahmood, K.; Zaheer, A.; Hussain, T.; Dawood, A.
Abstract: Spatial confinement effects on plasma parameters and surface morphology of laser-ablated Mg are studied by introducing a metallic blocker as well as argon (Ar) gas at different pressures. Nd: YAG laser at various fluences ranging from 7 to 28 J/cm 2 was employed to generate Mg plasma. Confinement effects offered by metallic blocker are investigated by placing the blocker at different distances of 6, 8, and 10 mm from the target surface; whereas spatial confinement offered by environmental gas is explored under four different pressures of 5, 10, 20, and 50 Torr. Laser-induced breakdown spectroscopy analysis revealed that both plasma parameters, that is, excitation temperature and electron number density initially are strongly dependent upon both pressures of environmental gases and distances of blockers. The maximum electron temperature of Mg plasma is achieved at Ar gas pressure of 20 Torr, whereas maximum electron number density is achieved at 50 Torr. It is also observed that spatial confinement offered by metallic blocker is responsible for the significant enhancement of both electron temperature and electron number density of Mg plasma. Maximum values of electron temperature and electron number density without blocker are 8335 K and 2.4 × 10 16 cm −3, respectively, whereas these values are enhanced to 12, 200 K and 4 × 10 16 cm −3 in the presence of blocker. Physical mechanisms responsible for the enhancement of Mg plasma parameters are plasma compression, confinement and pronounced collisional excitations due to reflection of shock waves. Scanning electron microscope analysis was performed to explore the surface morphology of laser-ablated Mg. It reveals the formation of ripples and channels that become more distinct in the presence of blocker due to plasma confinement. The optimum combination of blocker distance, fluence and Ar pressure can identify the suitable conditions for defining the role of plasma parameters for surface structuring.